OPTIMIZING LOCAL POTENTIAL THROUGH CREATIVE ECONOMY TRAINING FOR KARANGREJO VILLAGE MSMEs - Nur Lailiyah; Ingghar Gupti Nadia Kusmiaji; Naabilah Kuni Hafidhoh; Devi Rahma Septiani; Tiara Indriyani; Vinanda Ariyani; Novita Diana Austina; Iwan Marwan (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
This community service aims to optimize the local potential of Karangrejo Village through creative economy training for Micro, Small, and Medium Enterprises (MSMEs). Karangrejo Village has various local resources that have the potential to be developed into value-added products; therefore, this activity is designed to improve participants' skills in local wisdom-based product processing, digital marketing strategies, and sustainable business management. The activity implementation method includes socialization, practice-based training, and intensive mentoring. Training was provided interactively with the main materials including product innovation, branding and packaging, utilization of social media for marketing, and business financial management strategies. In addition, assistance was provided in implementing the training results to ensure program sustainability. Evaluation of the success of the activities was carried out through direct observation, interviews with participants, and analysis of business development after the training. The results of the activities showed an increase in participants' skills in developing creative products, understanding digital marketing strategies, and managing businesses more effectively. Some participating MSMEs have succeeded in increasing the competitiveness of their products with more attractive packaging designs and utilizing digital platforms for marketing. With this training, it is expected that the creative economy based on local potential in Karangrejo Village can develop sustainably and contribute to the welfare of the community.